2014
DOI: 10.1149/06123.0001ecst
|View full text |Cite
|
Sign up to set email alerts
|

PEMFC Contamination - Fundamentals and Outlook

Abstract: Contamination of proton exchange membrane fuel cells is coming to the forefront as commercialization activities multiply and fuel cell systems are confronted to field conditions away from the controlled laboratory environment. The recent progress achieved in understanding the disruptive effects of contaminants is reviewed. The analysis is focused on contaminant effects, contaminant sources, mechanisms, mitigation strategies and knowledge gaps in all these areas. IntroductionAs the commercialization of proton e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…4a showed that exposure to the individual contaminants at 1 A cm -2 actually may have improved fuel cell performance for NO 2 and BZ from a few mV at open circuit to approximately 0.011 V for NO 2 and 0.020 V for BZ at 1.2 A cm -2 . The reasons for the improved performance are not known, though improved performance subsequent to contaminant exposure was observed in other experiments with different contaminants (2,4). The experiments here should be performed again to assess the repeatability of the results.…”
Section: Irrecoverable Performance Lossmentioning
confidence: 83%
See 3 more Smart Citations
“…4a showed that exposure to the individual contaminants at 1 A cm -2 actually may have improved fuel cell performance for NO 2 and BZ from a few mV at open circuit to approximately 0.011 V for NO 2 and 0.020 V for BZ at 1.2 A cm -2 . The reasons for the improved performance are not known, though improved performance subsequent to contaminant exposure was observed in other experiments with different contaminants (2,4). The experiments here should be performed again to assess the repeatability of the results.…”
Section: Irrecoverable Performance Lossmentioning
confidence: 83%
“…This is an important consideration for developing PEMFCs for commercial applications because airborne contaminants can arise from many different sources including polluted air, geological emissions, and off-gassing from unstable compounds. Thus, the performance of the fuel cell can be affected in unknown ways depending on the quality of the local air (2). It is therefore important to study the effects of contaminants on performance and durability so that the operational lifetime of the PEMFCs can be maximized to facilitate full-scale commercialization and deployment of these devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEMFCs are expected to be durable but are exposed to a variety of contaminants either present in air and hydrogen or released by fuel cell system materials, which may be deleterious to performance. [1][2][3] Only a small fraction of the large number of likely contaminants have been investigated. For example, only 21 ambient air species from a list of more than 200 candidates were recently studied.…”
mentioning
confidence: 99%